2006
DOI: 10.1002/art.22119
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of skin disease in LUPUS‐prone MRL/FASlpr mice by means of a novel tylophorine analog

Abstract: Objective. To test the therapeutic effect of DCB-3503, a synthetic compound derived from a natural product that inhibits NF-B, on end-organ disease in the MRL-Fas lpr murine model of systemic lupus erythematosus (SLE).Methods. Eight-week-old female MRL/Fas lpr mice were treated intraperitoneally with a low (2 mg/kg) or high (6 mg/kg) dose of DCB-3503 for 10 weeks. Control groups were administered vehicle treatment alone (negative control) or 25 mg/kg cyclophosphamide (positive control). Mice were bled before (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…An attempt to treat MRL/lpr lupus mice with the NF-κB inhibitor DCB-3503, a tylophorine analog, resulted in almost complete abrogation of the inflammatory skin legions, but had little effect on renal histologic scores [26]. This may be because of the only partial reduction of anti-DNA antibodies achieved by the treatment.…”
Section: Systemic Lupus Erythematosus and Nf-κ Bmentioning
confidence: 86%
“…An attempt to treat MRL/lpr lupus mice with the NF-κB inhibitor DCB-3503, a tylophorine analog, resulted in almost complete abrogation of the inflammatory skin legions, but had little effect on renal histologic scores [26]. This may be because of the only partial reduction of anti-DNA antibodies achieved by the treatment.…”
Section: Systemic Lupus Erythematosus and Nf-κ Bmentioning
confidence: 86%
“…DCB-3503 (a tylophorine analog) has been commonly studied and showed antitumor activity [15,16] through mechanisms of inhibiting nucleic acid synthesis, RNA transcription, and protein synthesis [16][17][18]. Previously, DCB-3503 was reported to have anti-inflammatory effect in lupus and rheumatoid arthritis through suppressing innate immune response in our study [19,20]. In the current study, we synthesized (±)-tylophorine malate (NK-007), which had better water solubility (20 g/L at room temperature), whereas tylophorine (DCB-3503) could not be dissolved in water.…”
Section: Introductionmentioning
confidence: 87%
“…These findings demonstrate that both NF-κB signaling pathways are important for development of lupuslike disease associated with BAFF overproduction [56]. Remarkably, another study has shown that administration of DCB3503, a NF-κB inhibitor, for 10 weeks nearly abrogated inflammatory skin disease with little effect on histologic kidney disease in MRL/Fas(lpr) mice [57]. …”
Section: Nf-κb In Systemic Lupus Erythematosusmentioning
confidence: 92%